2015
DOI: 10.1093/icesjms/fsv198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high CO2 and warming on a Baltic Sea microzooplankton community

Abstract: Global warming and ocean acidification are among the most important stressors for aquatic ecosystems in the future. To investigate their direct and indirect effects on a near-natural plankton community, a multiple-stressor approach is needed. Hence, we set up mesocosms in a full-factorial design to study the effects of both warming and high CO2 on a Baltic Sea autumn plankton community, concentrating on the impacts on microzooplankton (MZP). MZP abundance, biomass, and species composition were analysed over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 83 publications
1
16
0
Order By: Relevance
“…The resilience of coastal plankton communities (bacteria, phytoplankton, micro- and mesozooplankton) towards future OA conditions was also demonstrated in earlier large scale mesocosm field and indoor studies [913, 57, 58]. In agreement with those results, we assume that low sensitivities for high CO 2 conditions are common for coastal plankton communities which are exposed to pronounced natural fluctuations in seawater pH.…”
Section: Discussionsupporting
confidence: 91%
“…The resilience of coastal plankton communities (bacteria, phytoplankton, micro- and mesozooplankton) towards future OA conditions was also demonstrated in earlier large scale mesocosm field and indoor studies [913, 57, 58]. In agreement with those results, we assume that low sensitivities for high CO 2 conditions are common for coastal plankton communities which are exposed to pronounced natural fluctuations in seawater pH.…”
Section: Discussionsupporting
confidence: 91%
“…The eCA concentration dropped more slowly in the ISCO treatment ( Supplementary Fig.2 Despite constant pumping of fresh ocean water into the sampling pool, heating of incubating bottles during the day because of the tropical climate (Supplementary Figure S1) was a clear limitation of our experiment. Previous studies did not detect a synergetic effect of OA and warming on plankton communities (Paul et al 2015, Horn et al 2016). But to exclude additional effects by warming, e.g., the decrease of heterotrophic flagellate biomass (Moustaka-Gouni et al 2016), we decided to compare effects of OA treatment only within but not between t0 and t2.…”
Section: Adaptations To the Ocean Acidification Treatmentmentioning
confidence: 88%
“…In their study of sediments from the Bornholm Basin, Dutz et al (2004) found high hatching rates of nauplii already in March and April, with strong increases in those rates as the incubation temperature increased. In mesocosm experiments, warming led to a reduced time-lag between the phytoplankton bloom and the microzooplankton biomass maximum (Horn et al, 2015). Therefore, early diatoms can be controlled by grazing, which implies lower and later algal peaks at higher temperatures (Gaedke et al, 2010).…”
Section: Indicator Of Food Web Changesmentioning
confidence: 99%